Okay Kevin : a story to help children discover how everyone learns differently - Dillon, James (Jessica Kingsley, 2017)
"Kevin never smiles at school, but he is different at home. He jumps up and down when his favorite football team scores a touchdown, and screams "Cannonball!" when he jumps into the swimming pool. But at school he feels that he isn't "okay". That is until one day when his teacher asks him to help out with the school store, and Kevin begins to realize that he has been "okay" all along.